The Concept of Liability Without Fault in Environmental Dispute Resolution In Indonesia - I.A. Pradnyandari Pidada; I Ketut Kasta Arya Wijaya (Pemuliaan Keadilan, 2025)
This study aims to analyze the application of the concept of liability without fault in resolving environmental disputes in Indonesia, by highlighting the legal basis, implementation, and challenges faced. The method used is a conceptual approach to examine relevant regulations and court decisions in order to obtain legal clarity regarding absolute responsibility in environmental pollution cases. The results of the study indicate that although this principle has been regulated in Article 88 of UUPPLH No. 32 of 2009 and reinforced by various derivative regulations, its implementation still faces obstacles, especially in terms of law enforcement, supervision, and compliance of business actors in carrying out environmental restoration obligations. Therefore, it is necessary to strengthen regulations, increase the capacity of law enforcement officers, and implement environmental assurance mechanisms to ensure the effectiveness of liability without fault in environmental protection in Indonesia.